Trimethoprim: An Old Antibacterial Drug as a Template to Search for New Targets. Synthesis, Biological Activity and Molecular Modeling Study of Novel Trimethoprim Analogs - Wróbel, Agnieszka (Molecules, 2019)
A new series of trimethoprim (TMP) analogs containing amide bonds (1–6) have been synthesized. Molecular docking, as well as dihydrofolate reductase (DHFR) inhibition assay were used to confirm their affinity to bind dihydrofolate reductase enzyme. Data from the ethidium displacement test showed their DNA-binding capacity. Tests confirming the possibility of DNA binding in a minor groove as well as determination of the association constants were performed using calf thymus DNA, T4 coliphage DNA, poly (dA-dT)(2) and poly (dG-dC)(2). Additionally, the mechanism of action of the new compounds was studied. In conclusion, some of our new analogs inhibited DHFR activity more strongly than TMP did, which confirms, that the addition of amide bonds into the analogs of TMP increases their affinity towards DHFR.